Law as Passion Systems Theory and Constitutional Theory in Peripheral Modernity - Nogueira de Brito, Miguel; Calabria, Carina; Portela L. Almeida, Fábio (Springer International Publishing : Imprint: Springer, 2021)
XVI, 251 p. 1 illus.